Penerapan Rekayasa Nilai (Value Engineering) pada Bangunan Rumah Susun Sederhana (Studi Kasus: Rusunawa Jongke Sleman) - Jap Yovita Natalie; Peter F. Kaming; A. Koesmargono (Jurnal Teknik Sipil, 2020)
The construction of apartment units which is certain to increase every year, of course must be followed by the construction and management of good and planned. In previous studies with the title "Life Cycle Cost Analysis in Simple Rental Flats in Yogyakarta Special Region" resulted in a very high final cost. In Construction Management (MK) know the science used to streamline and streamline costs and time. The science is known as Value Engineering (VE) or value engineering (Sesaria, 2012). There are several stages in VE, namely the Information Stage, the functional analysis stage, the creative stage, the development stage, the presentation stage. The quality of existing K350 concrete while the alternative quality used is K375. After using the VE method, the cost savings from existing K350 quality amounted to Rp 15,966,601,250.45 to Rp 13,211,701,701.00 alternative quality of K375. Cost savings of 17%.